Case report: A rare Salter–Harris V metaphyseal fatigue fracture of the knee in an adolescent patient with obesity - Gao, Chao; Feng, Ling Le; Zheng, Jiang Hua; Cao, Jin; Sun, Hua Jing (Frontiers in Pediatrics, 2023)
Stress fractures are rare, occurring in 1.5/100,000 high school athletes. High impact, repetitive loading participation in woman's sports, and being a white athlete have been identified as risk factors for stress fractures. Mostly treated conservatively, they are more common in the tibia (33%). Stress fractures requiring surgery, which are extremely rare, have been reported in the scaphoid, fifth metatarsal, and neck of femur. Herein, a 16-year-old adolescent patient with obesity presented with atypical knee pain after prolonged exercise. Advanced imaging revealed a stress fracture of the left tibia with a Salter–Harris type V fracture and varus deformity of the knee. We initially managed the fatigue fracture conservatively, followed by surgical correction of the varus deformity in the knee joint. The patient made a satisfactory recovery with equal limb length and no evidence of claudication. This is the first case of a proximal tibial metaphyseal stress fracture requiring surgery. The clinical manifestations of proximal tibial metaphyseal stress fractures and potential treatment strategies and the use of magnetic resonance for tibial stress fractures have been discussed. Understanding the location of unusual stress fractures can improve early diagnostic efficiency and reduce complication rates, healthcare costs, and recovery time.